Expired Tidal Volume and Respiratory Rate During Postnatal Stabilization of Newborn Infants Born at Term via Cesarean Delivery - Susana Baixauli-Alacreu, CM; Celia Padilla-Sánchez, CM; David Hervás-Marín, MSc; Inmaculada Lara-Cantón, MD; Alvaro Solaz-García, RN; Maria José Alemany-Anchel, PhD; Maximo Vento, MD, PhD (Elsevier, 2021)
Objective: To retrieve evolving respiratory measures in the first minutes after birth in normal neonates born at term using a respiratory function monitor. Study design: We evaluated newborn babies delivered at term via cesarean after uncomplicated pregnancies. Immediately after birth, a respiratory function monitor with an adapted flowmeter and a face mask were applied at 2, 5, and 10 minutes after birth for 90 seconds in each period. We analyzed expired and inspired tidal volume, respiratory rate (RR), percentage of leakage, and number of analyzed breaths in each individual infant's recording using a respiratory research software. Results: A total of 243 infants completed the study. The final data set included 59 058 (48.35%) valid observations for each of the variables representing the analysis of 32 801 breaths. With these data, we constructed a reference range with 10th, 25th, 50th, 75th, and 90th percentiles for expired tidal volume and RR. Tidal volumes plateaued earlier in female than in male infants. No correlation with delayed cord clamping, gestational age, maternal morbidity, or indication for cesarean delivery were established. Conclusions: We have constructed a reference range with percentiles for inspired and expired tidal volumes and RR in newborn babies born at term for the first 10 minutes after birth. Reference ranges can be employed for research and can be useful in the clinical setting to guide positive pressure ventilation in the delivery room.